Pursuing Environmental Justice: Obstacles and Opportunities—Lessons from the Field - Helen H. Kang (Washington University Journal of Law & Policy, 2009)
This Article addresses the flip-side of problem-solving courts: litigating problems that are so legally complex and affect so many constituents that it is difficult to identify the problem-solving mechanism, even if the problem is precisely defined.
Keywords: Access to justice; Environmental law; Environmental justice; Environmental justice communities; Environmental litigation; Pollution sources